GILLES DELEUZE – LIFE-WORK. INTELLECTUAL BIOGRAPHY - Banasiak, Bogdan (Hybris, 2025)
The text is an intellectual biography of the contemporary French philosopher, Gilles Deleuze. It includes his philosophical inspirations, friendships and, above all, all publications and their issues. However, first of all, it shows the profile of a man who, unable for health reasons to do what he dedicated his life to (think, write and teach), committed suicide. Finally, the text notes the reception of this act in French philosophical circles. All in all, it is a memory of the great philosopher and a tribute to his life-work.